O caso Ana: a transferência por meio da escrita na clínica psicanalítica - Diniz, Leidiane Francisco (2022)
In the context of the Covid-19 pandemic in Brazil, I helped a young woman through writing. The calls took place by text messages exchanged by WhatsApp (live) and then by chat on the videoconferencing platform Google Meet, in real time. Written assistance in the psychoanalytic clinic is quite unusual, which highlighted the importance of transference, in which the experience of speaking becomes its mainstay. However, in this context, we wonder if it would be possible to articulate the transference in writing and what is the status of transference through writing. This research aimed to investigate how the dynamics of transference was established in the form of written care in the psychoanalytic clinic, based on the construction of the clinical case, allowing a dive into Ana Clara's subjective-singular universe, as well as articulating possible elaborations on the signifiers of this young woman – her psychic economy and the psychic bond from her relationship with the Other – and her mark of singularity. The research methodology undertaken was anchored in psychoanalysis and in the construction of the clinical case, as an important device to compose the beacons of the enigma of this research. We built the Ana Clara case from the extraction of some signifiers that produced enigmas and concerns in the body of the analyst-researcher and resonated in the transference field, after diving into the signifiers and passing through the singularity marks of the case in question, we formulated the bases of the dynamics of the written transference as it was woven between the analyst-analyst, from the logical time: moment to see, time to understand and moment to conclude. We highlight the feasibility of transference being able to operate through writing. In the case reported, the transference that was woven through writing was through the imaginary rope. The written attendance presented some distinct particularities of the attendance by means of the speech that need to be considered, as the question of the time of the session that was experienced as eternal, there were few mistakes in the writing, because in the act of writing, the subject types, erases and rewrites before hitting Enter.